2013
DOI: 10.1186/1471-2474-14-276
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to osteoporosis regimens among men and analysis of risk factors of poor compliance: a 2-year analytical review

Abstract: BackgroundTo investigate adherence and patient-specific factors associated with poor compliance with osteoporosis regimens among men.MethodsIn this retrospective chart review study, we collected data on male patients with osteoporosis treated in accordance with therapeutic recommendations. Adherence was determined by the compliance and persistence of those patients who had been dispensed an osteoporosis regimen after an index prescription. All osteoporosis regimens were considered equivalent for the purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(60 reference statements)
0
8
0
Order By: Relevance
“… 9 Finally, but no less important, feedback to the patient on laboratory tests and bone densitometry results, his or her physical and psychological state, his or her socioeconomic situation, comorbidities, and polytherapy are likely to be determinants of adherence. 4 – 7 , 10 , 23 According to literature, this study showed that factors potentially associated with high adherence were: older age (>50 years), female sex, and some concomitant therapies (corticosteroids for systemic use, gastrointestinal diseases drugs). However, neurological and cardiovascular drugs and polytherapy continually reduced adherence throughout the follow-up ( P <0.001).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 9 Finally, but no less important, feedback to the patient on laboratory tests and bone densitometry results, his or her physical and psychological state, his or her socioeconomic situation, comorbidities, and polytherapy are likely to be determinants of adherence. 4 – 7 , 10 , 23 According to literature, this study showed that factors potentially associated with high adherence were: older age (>50 years), female sex, and some concomitant therapies (corticosteroids for systemic use, gastrointestinal diseases drugs). However, neurological and cardiovascular drugs and polytherapy continually reduced adherence throughout the follow-up ( P <0.001).…”
Section: Discussionmentioning
confidence: 89%
“…7 , 9 , 21 , 22 However, these regimens also do not ensure optimal effectiveness, as many observational studies have already reported. 6 , 23 Insufficient calcium intake and lack of vitamin D are the most common causes of nonresponse to antiosteoporosis therapy. 13 In particular, incidence of hypovitaminosis D in Italy is extremely high, especially among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of studies, a patient was defined as non-persistent with treatment if the time period between two consecutive prescription fills exceeded the length of the permissible gap. The most commonly used permissible gap was 30 days [ 5 , 30 , 32 40 , 44 , 49 , 52 , 55 , 56 , 58 , 61 , 65 ]; other commonly used permissible gaps were 60 and 90 days. In nine studies [ 6 , 31 , 40 42 , 45 , 47 , 64 , 66 ], patients were allowed to accumulate medicine (i.e., use supply from a previous prescription) and in 16 studies [ 6 , 30 32 , 34 , 39 , 40 , 44 46 , 52 , 54 , 55 , 57 , 61 , 63 ], they were allowed to switch between treatments during the study period (e.g., from alendronate to risedronate or from weekly to daily oral BPs).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 included studies, 39 reported at least one estimate of 12-month persistence with treatment (Fig. 4 ) [ 6 , 30 67 ] and 17 [ 5 , 6 , 31 , 32 , 37 , 45 , 46 , 48 , 50 52 , 55 , 58 , 59 , 61 , 64 , 65 ] reported at least one estimate of 24-month persistence (Table 3 ). Estimates of 12-month persistence varied widely, from 10 to 78 %, with the majority of estimates ranging from 30 to 60 %, and there was a large amount of heterogeneity between studies in the methods used (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, adherence to antiosteoporotic drugs, in general, is low in Taiwan. Low rates of adherence have been reported for alendronate (38.2 % patients with MPR ≥80 % at 12 months) in Taiwan using the NHIRD [ 32 ], and to bisphosphonates and calcitonin (37.5 % patients with MPR ≥80 % at 24 months) [ 33 ]. In a retrospective analysis of NHIRD data from 32,604 patients initiating bisphosphonate therapy in Taiwan, nearly 50 % of patients were found to be nonadherent (MPR < 80 %) to bisphosphonates at 3 months, and approximately 70 % were nonadherent at 1 year [ 34 ].…”
Section: Discussionmentioning
confidence: 99%